Population analysis of D6-like plasmid prophage variants associated with specific IncC plasmid types in the emerging Salmonella Typhimurium ST213 genotype. - Claudia Silva; Edmundo Calva; Marcos Fernández-Mora; José L Puente; Pablo Vinuesa (PLoS ONE, 2019)
The Salmonella enterica serovar Typhimurium sequence type 213 (ST213) emerged as a predominant genotype in Mexico. It is characterized by harboring multidrug resistance (MDR) IncC plasmids (previously IncA/C) and the lack of the Salmonella virulence plasmid (pSTV). Here we show that the D6-like plasmid prophage is present in most of the ST213 strains. We used the reported nucleotide sequence of YU39 plasmid (pYU39_89) to design a PCR typing scheme for the D6-like plasmid prophages, and determined the complete nucleotide sequences for the D6-like prophages of three additional ST213 strains (YU07-18, SL26 and SO21). Two prophage variants were described: i) a complete prophage, containing homologous sequences for most of the genetic modules described in P1 and D6 phages, which most likely allow for the lytic and lysogenic lifestyles; and ii) an incomplete prophage, lacking a 15 kb region containing morphogenesis genes, suggesting that it is defective. The tail fiber gene inversion region was the most divergent one between D6 and pYU39_89 genomes, suggesting the production of a distinct set of tail fibers, which could be involved in host range preferences. A glutaminyl-tRNA synthetase gene (glnS), which could be involved in providing host cell increased fitness or plasmid maintenance functions, was found in all D6-like genomes. Population level analysis revealed a biogeographic pattern of distribution of these plasmid-phages and specific associations with variants of MDR IncC plasmids. Statistically significant associations were found between the two prophage variants (p75 or p89), the type of IncC plasmids (I or II) and geographic isolation regions (Sonora, San Luis Potosí, Michoacán and Yucatán). This work integrates results from molecular typing, genomics and epidemiology to provide a broad overview for the evolution of an emergent Salmonella genotype.